26‐3: Difference in Optical and Hole‐injection Properties between Organic Material/Molybdenum Oxide Composite (OMOx) Layer and Hole‐injection Layer with Organic Acceptor. Issue 1 (30th May 2018) - Nakashima, Harue; Takita, Yusuke; Hashimoto, Naoaki; Nomura, Shiho; Suzuki, Tsunenori; Seo, Satoshi; Yamazaki, Shunpei
Abstract : A composite of an organic material and molybdenum oxide (OMOx) serves as a hole‐injection layer (HIL) in an OLED device even when the organic material has a deep HOMO level. Such "deep‐level OMOx" compounds exhibit several advantages in their optical and hole‐injection properties over general HILs that use organic acceptors.